2022
DOI: 10.3928/01477447-20211227-09
|View full text |Cite
|
Sign up to set email alerts
|

New Primary Total Knee Arthroplasty Components Versus Other Contemporary Types of Spacers for the Treatment of Chronic Periprosthetic Knee Infection With a Two-Stage Protocol

Abstract: The optimal type of antibiotic spacer for the treatment of a knee periprosthetic joint infection (PJI) remains a topic of debate. Although the ultimate goal of an antibiotic spacer is infection control, contemporary spacer iterations, such as the use of a new femoral component (NFC), may offer unique advantages. The primary goal of this study was to compare rates of infection control and functional outcomes between contemporary spacer types. We retrospectively reviewed 96 patients who underwent removal of a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…A total of 3421 studies were found through the electronic search and 21 studies were added after the cross-referenced research on the bibliographies of the examined full-text articles. After a preliminary analysis, a total of 87 studies reporting series of knee spacers used for two-stage treatment of PJI were included in this systematic review (1 randomized controlled trial, 3 prospective comparative cohort studies, 26 retrospective comparative cohort studies, 9 prospective case series, 48 retrospective case series [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 3421 studies were found through the electronic search and 21 studies were added after the cross-referenced research on the bibliographies of the examined full-text articles. After a preliminary analysis, a total of 87 studies reporting series of knee spacers used for two-stage treatment of PJI were included in this systematic review (1 randomized controlled trial, 3 prospective comparative cohort studies, 26 retrospective comparative cohort studies, 9 prospective case series, 48 retrospective case series [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Studies comparing static vs. articulated spacers were 1 RCT [ 43 ], 1 PCCS [ 22 ], and 16 RCCS [ 18 , 20 , 21 , 26 , 27 , 28 , 31 , 35 , 36 , 41 , 43 , 44 , 45 , 47 , 49 , 51 ]. In total, 34 series on static spacers [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] and 71 on articulated spacers [ 18 , 20 , 21 , 26 , 27 , 28 , 31 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High-dose antibiotic cement spacers for the treatment of PJI were found to be independent risk factors for acute kidney injury, which had a rate of 22.7% following the first stage of a planned 2-stage exchange versus 6.6% following a 1-stage exchange 36 . A study comparing knee spacer types (new femoral component, cement-on-cement, and static) found no difference in the odds of infection clearance and showed increased range of motion and improved ambulatory status prior to reimplantation utilizing the new-femoral-component spacer design 37 .…”
Section: Two-stage Exchangementioning
confidence: 99%